Reovirus exerts potent oncolytic effects in head and neck cancer cell lines that are independent of signalling in the EGFR pathway - Twigger Katie; Roulstone Victoria; Kyula Joan; Karapanagiotou Eleni M; Syrigos Konstantinos N; Morgan Richard; White Christine; Bhide Shreerang; Nuovo Gerard; Coffey Matt; Thompson Brad; Jebar Adel; et al. (BMC Cancer, 2012)
Abstract Background Reovirus exploits aberrant signalling downstream of Ras to mediate tumor-specific oncolysis. Since ~90% squamous cell carcinomas of the head and neck (SCCHN) over-express EGFR and SCCHN cell lines are sensitive to oncolytic reovirus, we conducted a detailed analysis of the effects of reovirus in 15 head and neck cancer cell lines. Both pre- and post-entry events were studied in an attempt to define biomarkers predictive of sensitivity/resistance to reovirus. In particular, we analysed the role of EGFR/Ras signalling in determining virus-mediated cytotoxicity in SCCHN. Methods To test whether EGFR pathway activity was predictive of increased sensitivity to reovirus, correlative analyses between reoviral IC50 by MTT assay and EGFR levels by western blot and FACS were conducted. Inhibition or stimulation of EGFR signalling were analysed for their effect on reoviral oncolysis by MTT assay, and viral growth by TCID50 assay. We next analysed the effects of inhibiting signalling downstream of Ras, by specific inhibitors of p38MAPK, PI3-K or MEK, on reoviral killing examined by MTT assay. The role of PKR in reoviral killing was also determined by blockade of PKR using 2-aminopurine and assaying for cell survival by MTT assay. The apoptotic response of SCCHN to reovirus was examined by western blot analysis of caspase 3 cleavage. Results Correlative analyses between reoviral sensitivity and EGFR levels revealed no association. Intermediate sub-viral and core particles showed the same infectivity/cytotoxicity as intact reovirus. Therefore, sensitivity was not determined by cell entry. In 4 cell lines, oncolysis and viral growth were both unaffected by inhibition or stimulation of EGFR signalling. Inhibition of signalling downstream of Ras did not abrogate reoviral oncolysis and, in addition, modulation of PKR using 2-aminopurine did not alter reovirus sensitivity in resistant cell lines. Caspase 3 cleavage was not detected in infected cells and oncolysis was observed in pan-caspase inhibited cells. Conclusions In summary, reovirus is potently oncolytic in a broad panel of SCCHN cell lines. Attempts to define sensitivity/resistance by analysis of the EGFR/Ras/MAPK pathway have failed to provide a clear predictive biomarker of response. Further analysis of material from in vitro and clinical studies is ongoing in an attempt to shed further light on this issue.